1995
DOI: 10.1021/bi00046a007
|View full text |Cite
|
Sign up to set email alerts
|

How Allosteric Effectors Can Bind to the Same Protein Residue and Produce Opposite Shifts in the Allosteric Equilibrium

Abstract: Monoaldehyde allosteric effectors of hemoglobin were designed, using molecular modeling software (GRID), to form a Schiff base adduct with the Val 1 alpha N-terminal nitrogens and interact via a salt bridge with Arg 141 alpha of the opposite subunit. The designed molecules were synthesized if not available. It was envisioned that the molecules, which are aldehyde acids, would produce a high-affinity hemoglobin with potential interest as antisickling agents similar to other aldehyde acids reported earlier. X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 25 publications
(40 reference statements)
10
53
0
Order By: Relevance
“…the effectors potency and/or direction of shift) is due not only to where the molecule binds, but also how it interacts with the Hb dimer-dimer interface to stabilize or destabilize that allosteric state. 48,49 …”
Section: Hemoglobin – a Target For Drug Designmentioning
confidence: 99%
See 1 more Smart Citation
“…the effectors potency and/or direction of shift) is due not only to where the molecule binds, but also how it interacts with the Hb dimer-dimer interface to stabilize or destabilize that allosteric state. 48,49 …”
Section: Hemoglobin – a Target For Drug Designmentioning
confidence: 99%
“…Interestingly, there are several aromatic aldehyde AEHs that also bind to the α-cleft to form Schiff-base with αVal1 nitrogen, but instead of left-shifting the OEC, they rather decrease Hb affinity for oxygen. 40,48,49,90 An ortho or para substituted carboxylate moiety (relative to the aldehyde functional group) in these right-shifters, e.g. , 5-formylsalicylic acid (5-FSA; Fig.…”
Section: Development Of Allosteric Modifiers Of Hb To Treat Sicklementioning
confidence: 99%
“…13,16,17 Unlike the above-mentioned aromatic aldehydes, there are other classes of aromatic aldehydes that bind Hb and preferentially stabilize the T-state relative to the R-state resulting in a decrease in Hb affinity for oxygen. 11,12,25,26 These compounds as expected promote sickling.…”
Section: Introductionmentioning
confidence: 81%
“…We have previously shown that aromatic aldehydes that form Schiff-base adduct with the N-terminal Val1 nitrogen and modify Hb may exhibit different allosteric behaviors (increase or decrease Hb affinity for oxygen), with the direction and magnitude of the allosteric shift dependent on preferential binding and/or stabilization of one Hb state (R or T) over the other. 11,25,26 For example, 5-HMF binds to both liganded and unliganded Hb, but significantly weaker to the latter; thus preferentially stabilizing the R-state and increasing Hb oxygen affinity. 11,15 It is likely that 5-NMFC and 5-CMFC bind and confer more stabilization to the T-state than 5-PMFC, in part explaining the significant differences in their P 50 and antisickling activities.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were designed to bind at the FBP binding site, suggesting that an allosteric effector can bind to the same site, but produce opposite allosteric properties. We have reported this duality of action with binding at the same allosteric site in hemoglobin [51] [52]. Based on these results, a general hypothesis was proposed: that an effector ability to shift the allosteric equilibrium (i.e., the effectors potency) is due not only to where the molecule binds to, but also which residues it interacts with at the binding site This general concept can also be applied to R-PK, as we observed not only opposite effects, but also varying allosteric potencies among the tested compounds.…”
Section: Kinetics Of R-pk In the Presence Of Compoundmentioning
confidence: 87%